ANALISIS NILAI SPF PADA PRODUK TABIR SURYA MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Ninis Yuliati; Silvia Putri Agustini; Fery Eko Pujiono; Tri Ana Mulyati (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2023)
Indonesia is a country with high sun exposure and the potential for high sun exposure. These rays are UVA (290-320) and UVB (320-400) rays which have both good and bad effects on humans. The formation of Vitamin D and provitamin D is a benefit, but with severe ozone depletion the UV rays produced can be harmful to human health and can cause cancer. Sunscreen which is used to protect the health of human skin from the negative effects of solar radiation and can absorb light exposure is often used in daily life as a cosmetic whose effectiveness in light absorption is based on the value of the sun protection factor (SPF), hereby to determine the value and category SPF value on sunscreen products with UV-Vis Spectrophotometry method to find out its effectiveness. By using the sampling method of Non Probability Sampling. In the determination, mixing 3 samples of sunscreen, the determination of this SPF value is a measure of the protection of sunscreen cream preparations against Ultraviolet rays. The higher the SPF value, the greater the protective effect against sunburn. The results obtained deviation of 1.04 with an average SPF in this study was 4.1 which was included in the SPF category with minimal protection.